FAKTOR – FAKTOR YANG MEMPENGARUHI DISIPLIN KERJA GURU (Suatu Studi Pada SMP Negeri Se Kecamatan Muara Jawa) - Nur Agus Salim (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
This study aims to determine the factors that influence the discipline of teachers' work. The study population was 56 teachers of SMP Negeri scattered at 2 schools. Given the limited population, this study is a population study where the sample is the entire population of the State school teachers in Muara Jawa.The research method using correlation and regression. The study found that the variables that affect the discipline of teachers 'work is variable Principal Leadership (X1) at a very strong level of closeness, namely 0.912, teachers' work motivation (X2) with variable at a strong level of closeness, that is equal to 0.865.It is concluded that the increase in labor discipline teachers of SMP Negeri Muara Jawa Se can be done by improving the leadership of the principal and teachers work motivation. Researchers suggested that the relevant parties can make efforts to promote the leadership of the principal and teachers work motivation in order to achieve a good working discipline at teachers of SMP Negeri In Muara Jawa.Keywords : Leadership Principal, Teacher Work Motivation, Discipline Work